2008
DOI: 10.1117/12.810575
|View full text |Cite
|
Sign up to set email alerts
|

Effective diaphragm area of spring-supported capacitive MEMS microphone designs

Abstract: Capacitive (condenser) MEMS microphones have been developed using various design and fabrication techniques to improve performance. Mechanical sensitivity of a condenser MEMS microphone can be increased by reducing the residual stress of the diaphragm using several design approaches including corrugated diaphragms, and in recent years, various spring type diaphragms. The electrical sensitivity of the condenser microphone is proportional to the deflection of the diaphragm, however, the parabolic deflection of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
3
0
4
Order By: Relevance
“…Weigold et al [13] was using a spring-supported, thin polysilicon diaphragm fabricated on silicon on insulator (SOI) wafer to achieve a sensitivity of -47 dB (ref 1 V/Pa) with the amplifier circuit. Another high sensitivity of up to 8.2 mV/Pa was reported by Fuldner et al [9] using a spring type diaphragm membrane of 1 mm in diameter and low bias voltage of 1 V. Mohamad et al [12,14] has also demonstrated that a specially designed spring-supported diaphragm can easily achieve up to 100 times higher mechanical sensitivity and 1.5 times higher capacitance change compared to the edge-clamped diaphragm of the same size.…”
Section: Introductionmentioning
confidence: 84%
“…Weigold et al [13] was using a spring-supported, thin polysilicon diaphragm fabricated on silicon on insulator (SOI) wafer to achieve a sensitivity of -47 dB (ref 1 V/Pa) with the amplifier circuit. Another high sensitivity of up to 8.2 mV/Pa was reported by Fuldner et al [9] using a spring type diaphragm membrane of 1 mm in diameter and low bias voltage of 1 V. Mohamad et al [12,14] has also demonstrated that a specially designed spring-supported diaphragm can easily achieve up to 100 times higher mechanical sensitivity and 1.5 times higher capacitance change compared to the edge-clamped diaphragm of the same size.…”
Section: Introductionmentioning
confidence: 84%
“…Diyaframın boyutu ve gerginliği, mikrofonun akustik performansının belirlenmesinde çok önemli bir rol oynar (Kim, Lee, Lee, Lee, & Park, 2007). Diyafram ile arka plaka arasındaki hava boşluğu bir kapasitör görevi görür ve diyaframın hareketi kapasitansı değiştirerek bir elektrik sinyali üretir (Mohamad, Lovenitti, & Vinay, 2008). Kapsül olarak adlandırılan bu sistem bir kondansatör görevi görmektedir.…”
Section: Kondansatör (Condenser) Mikrofonunclassified
“…Diyaframın boyutu ve gerginliği, mikrofonun akustik performansının belirlenmesinde çok önemli bir rol oynar (Kim, Lee, Lee, Lee, & Park, 2007). Diyafram ile arka plaka arasındaki hava boşluğu bir kapasitör görevi görür ve diyaframın hareketi kapasitansı değiştirerek bir elektrik sinyali üretir (Mohamad, Lovenitti, & Vinay, 2008). Kapsül olarak adlandırılan bu sistem bir kondansatör görevi görmektedir.…”
Section: Kondansatör (Condenser) Mikrofonunclassified